If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 24 = 20x + 26 Reorder the terms: 24 + 12x = 20x + 26 Reorder the terms: 24 + 12x = 26 + 20x Solving 24 + 12x = 26 + 20x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20x' to each side of the equation. 24 + 12x + -20x = 26 + 20x + -20x Combine like terms: 12x + -20x = -8x 24 + -8x = 26 + 20x + -20x Combine like terms: 20x + -20x = 0 24 + -8x = 26 + 0 24 + -8x = 26 Add '-24' to each side of the equation. 24 + -24 + -8x = 26 + -24 Combine like terms: 24 + -24 = 0 0 + -8x = 26 + -24 -8x = 26 + -24 Combine like terms: 26 + -24 = 2 -8x = 2 Divide each side by '-8'. x = -0.25 Simplifying x = -0.25
| (7(x-8))/6=-2x | | 0.5(4-8x)-8x=-62 | | y^2-4y+4=x-7 | | x^3+5x^2-66x=0 | | 21/4+21/4= | | X-x/2-8=x/4 | | 4cos^3x=cosx | | y^3-6y^2+6.211180124=0 | | y-5.7=-0.95(x-2) | | 3cos^2x-x-1=0 | | X^2/25-y^2=1 | | 4x^2/3-3x^1/3=10 | | 30=4y+2y | | 3/x-1/7=5/x | | 15w-6w=54 | | 23-4=15 | | b-32=63 | | 3km*2km= | | 2(m+3)+3m=24 | | =2.5E-6 | | (-12.7z^3-14z)+(-8.9z^3+12z+2)= | | g(-3)=4x-3 | | 60=-16t^2+20t | | -3(2x-3)=(-6x+9) | | 5(y-2)/2=-2y | | -3+x+5=5 | | -2x-(3x+8)=6x-38 | | 12x+4=12x-2 | | x/2.3=6 | | 8x=-12+5 | | -11+x-4=2 | | (6/5x)-(8/x)=2 |